Oral Administration of Fucosylated Chondroitin Sulfate Oligomers in Gastro-Resistant Microcapsules Exhibits a Safe Antithrombotic Activity - Yan, Lufeng; Zhu, Mengshan; Wang, Danli; Tao, Wenyang; Liu, Donghong; Zhang, Fuming; Linhardt, Robert J.; Ye, Xingqian; Chen, Shiguo (Thrombosis and Haemostasis, 2020)
Fucosylated chondroitin sulfate (FCS) polysaccharide isolated from sea cucumber has potent anticoagulant activity. Based on its resistance to the enzymes present in vertebrates, it may serve as an anticoagulant and shows antithrombotic effects when delivered through gastro-resistant (GR) tablets. However, due to the multiple plasma targets of FCS polysaccharide in the coagulation pathway, bleeding can occur after its oral administration. In the current study, we used FCS oligomers, in particular a mixture of oligosaccharides having 6 to 18 saccharide units, as the active ingredient in GR microcapsules for oral anticoagulation. In a Caco-2 model, the FCS oligomers showed higher absorption than native FCS polysaccharides. Oral administration of FCS oligomer-GR microcapsules provided a dose-dependent, prolonged anticoagulant effect with a selective inhibition of the intrinsic coagulation pathway when compared with subcutaneous administration of FCS oligomers or oral administration of unformulated FCS oligomers or native FCS-GR microspheres. Continued oral administration of FCS oligomer-GR microcapsules did not result in the accumulation of oligosaccharides in the plasma. Venous thrombosis animal models demonstrated that FCS oligomers delivered via GR microcapsules produced a potent antithrombotic effect dependent on their anticoagulant properties in the plasma, while oral administration of unformulated FCS oligomers at the same dose exhibited a weaker antithrombotic effect than the formulated version. Oral administration of FCS oligomer-GR microcapsules resulted in no bleeding, while oral administration of native FCS-GR microcapsules resulted in bleeding (p < 0.05). Our present results suggest that a FCS oligomer-GR microcapsule formulation represents an effective and safe oral anticoagulant for potential clinical applications.
Keywords: fucosylated chondroitin sulfate oligomers; gastro-resistant microcapsules; oral administration; anticoagulant and antithrombotic activities; bleeding tendency